Effects of blood-flow restricted exercise versus conventional resistance training in musculoskeletal disorders—a systematic review and meta-analysis - Stian Langgård Jørgensen; Signe Kierkegaard-Brøchner; Marie Bagger Bohn; Mathias Høgsholt; Per Aagaard; Inger Mechlenburg (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Objective To compare the effect of low-load blood flow restricted resistance training (BFR-RT) versus high-load resistance training (HL-RT) on muscle strength, muscle mass, physical function, patient-reported outcomes, and adherence to training in clinical musculoskeletal populations. Data sources Web of Science, Cochrane Central, Medline, Embase, SportDiscus was searched on the 30th May 2022. Review methods This study was conducted as a systematic review and meta-analysis. Randomized Controlled Trials (RCTs) were included if they (i) included patients, (ii) comprised of a BFR-RT intervention protocol and a group who performed HL-RT (≥ 70%1RM) for at least eight exercise sessions, and (iii) involved at least 1 exercise that targeted the lower limbs. The Cochrane Risk of Bias tool was used to evaluate the risk of bias. The meta-analyses were performed using a random effects model with an adjustment to the confidence interval. Results Seven RCTs comprising 303 participants (BFR-RT: n = 151; HL-RT: n = 152) were identified. HL-RT and BFR-RT showed similar gains in dynamic (1-10RM) knee extensor strength and leg press strength, quadriceps cross sectional area, sit-to-stand performance, and patient reported pain and function. There was a moderate effect favoring BFR-RT for increasing maximal isometric knee extensor strength. The grading of certainty in evidence was low-to-very low for all outcome variables. Conclusion This systematic review and meta-analysis extends our current knowledge about BFR-RT and HL-RT as equally effective exercise methods for inducing gains in maximal muscle strength in healthy populations, by now also comprising patients suffering from various clinical musculoskeletal conditions. The certainty in the estimates was low-to-very low, prompting the inclusion of future higher-quality trials. Trial registration PROSPERO ID (CRD42022337173). Registered June 18th 2022.